OBESITY AND SLEEP DISTURBANCE IN CHILDREN - O. V. Kozhevnikova; L. S. Namazova-Baranova; Yu. S. Mytnikova; E. A. Abashidze; T. V. Margieva; A. E. Paltseva (Union of pediatricians of Russia, 2017)
Obesity - one of the main challenges for the public health around the world in the twenty-first  century. It is a leading risk factor for serious complications of the cardiovascular system resulting in 17 million deaths worldwide each year. In Russia only, among young people, the prevalence of the disease is 11,8-16,6% and growing, especially in the last decade. Along with obesity, the problem of sleep disorder becomes increasingly urgent. One of the main factors of sleep disorders with children is the obstructive sleep apnea syndrome (OSA), which is considered  as one of the main causes  of cardiovascular  problems  development  among adults. Depending  on the methods for its diagnosis, children's OSA occurs in 1-13% of cases, and there is reason to believe that it often remains undiagnosed. With sleep disorders, children get stuck in a vicious circle that causes the development of insulin resistance, nocturnal hypoglycemia, and changes in carbohydrate metabolism.